STRATEGI PENGEMBANGAN AGROWISATA BELIMBING DEWA KELURAHAN PASIR PUTIH KOTA DEPOK - administrator, administrator; Dahliani, Putri Millenia; Prasetyo, Agus Subhan; Mariyono, Joko (Fakultas Pertanian Universitas Wijaya Putra, 2023)
Agrotourism is a tourism activities that utilize the potential of agriculture as a tourist attraction. Internal and external analysis and strategies for developing agro-tourism are expected to be able to increasde farmers income. Development is needed so that agrotourism can survive and have future strategies in dealing with the crisis during the covid19 pandemic. This research has purposes for 1). It analyzed the impact of the covid-19 pandemic on the development of Belimbing Dewa Agrotourism, Pasir Putih Village, Depok City. 2). Analyzing the internal and external environment of Belimbing Dewa Agrotourism, Pasir Putih Village, Depok City. 3). analyze the developed Belimbing Dewa Agrotourism strategy, Pasir Putih Village, Depok City, during the covid-19 pandemic. This research was conducted from December 20, 2021, to February 9, 2022, at Belimbing Dewa Agrotourism, Pasir Putih Village, Depok City. The study used survey methods and data collection methods by interview and observation. Respondents in this study were 30 people from agro-tourism visitors. The data analysis method used quantitative descriptive analysis. The results showed that the impact of the covid-19 pandemic on Belimbing Dewa Agrotourism could be sawed from a decrease in visitor visits, a reduction in worker salaries and layoffs, and a decline in cooperatives. MSME income, external and internal environmental factors that influence the affordability of entrance tickets and product prices, and the lack of funds, the opening of opportunities for economic improvement for the surrounding community, the challenge factor that must be faced is the unstable economic factor due to the covid-19 pandemic, based on the analysis of the position matrix shows that Belimbing Dewa Agrotourism is in quadrant 2. Hence, the strategy that must be applied is a diversification strategy.